INVESTIGATING UNIVERSITY STUDENT’S ACCEPTANCE OF VIRTUAL AND REMOTE LABS IN THEIR LEARNING - Nasution, Nanda Eska Anugrah; Rizka, Chairany (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
With the advancement of information and technology, virtual and remote laboratories have become supplementary or extra tools for hands-on biology laboratories. In this study, we modified the technology acceptance model to incorporate three additional external variables derived from flow theory in predicting students' acceptance and use of virtual and remote laboratories. This research included 145 college students. These students used virtual and remote laboratories for at least three months. The learning subjects in this research are deoxyribonucleic acid extraction, polymerase chain reaction, gel electrophoresis, deoxyribonucleic acid microarray, and flow cytometry. Using SPSS 25.0, a multiple regression analysis was performed to test the structural model hypothesis. This study validated the association between the basic variables used in the technology acceptance model: perceived ease of use, perceived usefulness, attitudes toward using, behavioral intention, and actual use. There were no surprising discoveries for the technology acceptance model's primary variables. Concentration and perceived enjoyment in the flow theory variables have an extensive relationship with the technology acceptance model variables, perceived usefulness, and perceived ease of use. Meanwhile, one flow theory variable, time distortion, exhibits no significant relationship with perceived usefulness or ease of use. Abstrak: Laboratorium virtual dan jarak jauh menjadi tren yang dimanfaatkan sebagai alat bantu praktikum biologi. Kami memodifikasi model penerimaan teknologi dalam penelitian ini dengan memasukkan tiga variabel eksternal tambahan yang berasal dari teori flow dalam memprediksi bagaimana mahasiswa menerima dan menggunakan laboratorium virtual dan jarak jauh. Penelitian melibatkan 145 mahasiswa. Para mahasiswa ini telah menggunakan laboratorium virtual dan jarak jauh setidaknya tiga bulan. Materi pembelajaran penelitian ini adalah ekstraksi asam deoksiribonukleat (DNA), polymerase chain reaction (PCR), gel electrophoresis, deoxyribonucleic acid microarray, dan flow cytometry. Hubungan antara variabel dasar yang digunakan dalam technology acceptance model yaitu kemudahan penggunaan yang dirasakan (perceived ease of use), kebergunaan yang dirasakan (perceived usefulness), sikap (attitudes toward using), niat perilaku (behavioral intention), dan penggunaan sebenarnya (actual use) divalidasi dalam penelitian ini. Data yang terkumpul dianalisis regresi berganda dengan bantuan SPSS 25. Tidak ada penemuan mengejutkan untuk variabel utama technology acceptance model. Variabel konsentrasi (concentration) dan kesenangan yang dirasakan (perceived enjoyment) pada teori flow memiliki hubungan yang signifikan dengan variabel technology acceptance model, kebergunaan yang dirasakan dan kemudahan penggunaan yang dirasakan. Sedangkan satu variabel teori flow, distorsi waktu (time distortion) tidak menunjukkan hubungan yang signifikan dengan kebergunaan yang dirasakan atau kemudahan penggunaan yang dirasakan.